Language teacher recognition narratives of Filipino English teachers in Japan - Stewart, Alison (New perspectives on language and education, 2020)
"This book presents the career narratives of an under-researched group of teachers: immigrant Filipino teachers of English working mainly with young and very young learners in Japan. It provides a nuanced and revealing critique of poststructuralist views of identity and proposes recognition theories as an alternative perspective"--